Understanding Artificial Intelligence and Predictive Analytics: A Clinically Focused Review of Machine Learning Techniques. Issue 3 (18th March 2022) - Cho, Brian; Geng, Eric; Arvind, Varun; Valliani, Aly A.; Tang, Justin E.; Schwartz, John; Dominy, Calista; Cho, Samuel K.; Kim, Jun S.
Abstract : » Machine learning and artificial intelligence have seen tremendous growth in recent years and have been applied in numerous studies in the field of orthopaedics. » Machine learning will soon become critical in the day-to-day operations of orthopaedic practice; therefore, it is imperative that providers become accustomed to and familiar with not only the terminology but also the fundamental techniques behind the technology. » A foundation of knowledge regarding machine learning is critical for physicians so they can begin to understand the details in the algorithms that are being developed, which provide improved accuracy compared with clinicians, decreased time required, and a heightened ability to triage patients.